Bio-renewable furan-based poly(ester amide)s: Synthesis, structure, spectroscopic and mechanical properties of poly(hexylene 2,5-furandicarboxylate)-co-poly(propylene furanamide)s (PHF-co-PPAF) - Agata Zubkiewicz; Izabela Irska; Konrad Walkowiak; Jerzy Dryzek; Sandra Paszkiewicz (eXPRESS Polymer Letters)
In this work, new furan-based poly(ester amide)s of various compositions were synthesised by the melt polycondensation method. The chemical structure and composition were determined by nuclear magnetic resonance spectroscopy (1H NMR) and Fourier transform infrared (FTIR) analyses. The optical properties were studied by UV-Vis spectroscopy. The thermal properties were investigated by means of differential scanning calorimetry (DSC). The thermo-oxidative stability of PEAs was also tested. Additionally, the free volume by positron annihilation lifetime spectroscopy (PALS) technique and mechanical properties were examined. It was found that the incorporation of poly(propylene furanamide) (PPAF) units significantly affects the thermal and mechanical properties of co-polymers based on poly(hexylene 2,5-furandicarboxylate) (PHF). Depending on the composition, both semi-crystalline and amorphous co-polymers were obtained. Moreover, the values of the free volume radius (R) and the free volume fractions (fv) were strongly affected by the mole fraction of PPAF units.